2013
DOI: 10.1371/journal.pone.0069109
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence Rates of Mental Disorders in Chilean Prisons

Abstract: ObjectiveHigh rates of mental disorders have been reported for prison populations worldwide, particularly in low- and middle-income countries (LMICs). The present study aimed to establish prevalence rates of mental disorders in Chilean prisoners.MethodA nationwide random sample of 1008 prisoners was assessed in 7 penal institutions throughout Chile. Twelve-month prevalence rates were established using the Composite International Diagnostic Interview (CIDI) and compared to the prevalence rates previously publis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
46
3
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 58 publications
(58 citation statements)
references
References 25 publications
4
46
3
5
Order By: Relevance
“…We aimed to recruit a total sample of 150 participants. The sample size was expected to yield percentage estimates with reasonable 95% confidence intervals (CI) for the total sample, i. e. 10% (95% CI: 5-15) or 20% (95% CI: [14][15][16][17][18][19][20][21][22][23][24][25][26]. Prisoners with all types of verdict such as people in detention, remand prisoners and convicted prisoners were included in the study.…”
Section: Samplementioning
confidence: 99%
See 1 more Smart Citation
“…We aimed to recruit a total sample of 150 participants. The sample size was expected to yield percentage estimates with reasonable 95% confidence intervals (CI) for the total sample, i. e. 10% (95% CI: 5-15) or 20% (95% CI: [14][15][16][17][18][19][20][21][22][23][24][25][26]. Prisoners with all types of verdict such as people in detention, remand prisoners and convicted prisoners were included in the study.…”
Section: Samplementioning
confidence: 99%
“…The priority is then to develop adequate treatments, which acknowledge the primary substance of addiction and comorbidities with other mental disorders, the so called 'dual disorders' [18]. Previous research has demonstrated, with respect to nicotine addiction of prisoners, that treatment was superior to mere forced 5 abstinence in smoke free jails, which by itself had hardly any affect on the addiction after release [19].…”
Section: Introductionmentioning
confidence: 99%
“…convicts in Chile (Mundt et al, 2013). In most places, major depression at admission to prison remains untreated.…”
mentioning
confidence: 99%
“…Con respecto a la PD, se han encontrado prevalencias entre 6 y 43.3% (Baillargeon et al, 2010;Butler et al, 2011;Fazel & Seewald, 2012;Lukasiewicz et al, 2009). Entre los OTP más prevalentes en personas en prisión con TCS, se encuentran los trastornos de personalidad; destacan el trastorno antisocial de la personalidad, los trastornos psicóticos, de ansiedad, del estado de ánimo y por déficit de atención (Butler et al, 2011;Casares-López et al, 2010;Fazel & Baillargeon, 2011;Fazel & Danesh, 2002;Fazel & Seewald, 2012;Fazel & Yu, 2011;Lukasiewicz et al, 2009;Konstenius et al, 2015;Mundt et al, 2013). En la Tabla 2 se presentan algunos estudios observacionales específicos en patología dual en entornos penitenciarios.…”
Section: Mini Entrevista Neuropsiquiátrica Internacional (Mini)unclassified
“…Diversos estudios han asociado los trastornos mentales con dificultades de ajuste al ambiente penitenciario, lo cual aumenta el riesgo de presentar abuso y padecer violaciones a los derechos humanos, asimismo dificulta la reintegración social e incrementa las probabilidades de indigencia o reingreso a la cárcel (Mundt et al, 2013;Colmenares-Bermúdez, Romero Mendoza, Rodríguez Ruiz, Durand-Smith, & Saldívar Hernández, 2007;Fazel & Seewald, 2012;McNiel, Binder, & Robinson, 2005). Se ha documentado que es más probable que los reclusos con PD presenten múltiples encarcelamientos o les sea revocada la libertad condicional, comparados con quienes no tienen PD (Baillargeon et al, 2009;Baillargeon et al, 2010;Black et al, 2010;Pickard & Fazel, 2013).…”
Section: Implicaciones De Salud Públicaunclassified